2019
DOI: 10.20524/aog.2019.0374
|View full text |Cite
|
Sign up to set email alerts
|

The impact of colonoscopy indication on polyp detection rate

Abstract: Background Adenoma/polyp detection rates are considered to be among the most important quality indicators of colonoscopy and are key measures of a quality procedure. However, they are designed for use in the screening setting and are not amenable to other colonoscopy indications. Little is known about their significance in other colonoscopy indications. We aimed to evaluate the impact of the various indications on polyp detection rate (PDR). Methods This was a retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
1
6
1
Order By: Relevance
“…Power spectra (dB) were computed over 2-minute long epoch of EEG, partitioned into 512-point epochs, and averaged, yielding a temporal resolution of 2 Hz. Normalized power was calculated as the fraction of a specific frequency power, including delta (0.5-4 Hz), theta (4-8 Hz), alpha (8-12 Hz), spindle (12)(13)(14)(15), beta (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and gamma (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), in the total power over all frequency bands from 0.5-40 Hz. The mean powers in percent for pre (1), post saline or caffeine injection (2), during 1.2% isoflurane (3) and before RORR (4) were computed by the MATLAB program.…”
Section: Power Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…Power spectra (dB) were computed over 2-minute long epoch of EEG, partitioned into 512-point epochs, and averaged, yielding a temporal resolution of 2 Hz. Normalized power was calculated as the fraction of a specific frequency power, including delta (0.5-4 Hz), theta (4-8 Hz), alpha (8-12 Hz), spindle (12)(13)(14)(15), beta (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and gamma (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), in the total power over all frequency bands from 0.5-40 Hz. The mean powers in percent for pre (1), post saline or caffeine injection (2), during 1.2% isoflurane (3) and before RORR (4) were computed by the MATLAB program.…”
Section: Power Spectramentioning
confidence: 99%
“…Our earlier studies in rats showed that caffeine was equally effective at accelerating emergence from propofol anesthesia as it was in isoflurane anesthesia [15]. Light propofol anesthesia is commonly used in a variety of procedures including colonoscopies and to prevent movement in MRI exams [18][19][20][21]. It will be important to determine whether caffeine can reverse the effects of other anesthetics, like propofol and dexmedetomidine, in a similar manner to that observed for isoflurane, as these drugs and their effects can stay in the body long after the termination of the anesthetic agent.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…In the case of polyps, each one was excised and histologically evaluated. With regard to the quality indices of the examination, for colonoscopies we calculated the adenoma detection rate (ADR), the adenoma detection index (ADI), the polyp detection rate (PDR), the polyp detection index (PDI) [ 13 ] and the cecal intubation rate on the general patient population, on the patient population divided by gender and the patient population that underwent a screening colonoscopy through the regional program to screen for colorectal cancer. After the procedures, each patient was safely discharged if his Aldrete [ 14 ] score ( Table 3 ) was higher than 8.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary outcomes included the polyp detection rate (PDR), the mean number of adenomas per colonoscopy (APC) and, the advanced adenoma detection rate (AADR). ADR, PDR and AADR are defined by the proportion of patients aged 50 years or older undergoing screening or diagnostic colonoscopy with at least one histologically proven adenoma, polyp, or advanced adenoma, respectively 5 9 10 . Advanced adenoma was defined as a lesion with villous features, high-grade dysplasia, or size greater than 10 mm.…”
Section: Methodsmentioning
confidence: 99%